LEVERAGING INSTAGRAM FOR FOSTERING DIVERSITY IN LEARNING ENGLISH AS A FOREIGN LANGUAGE - Siti Nur Hanifah; Daviq Rizal (PROGRES PENDIDIKAN, 2026)
This study explores the potential of Instagram in enhancing cultural diversity within the context of English as a Foreign Language (EFL) instruction. The study aims to investigate how Instagram's visual and interactive elements contribute to expanding cultural aspects in English language learning. With 40 participants from various universities, the study employs a structured questionnaire to analyze Instagram's impact on language learning. Results indicate that Instagram is effective, particularly in improving Intercultural Communication Effectiveness (ICE). Visual content, hashtags, and participation in intercultural activities are identified as key factors supporting positive learning experiences. The study concludes that Instagram not only serves as an effective language learning tool but also holds the potential to enrich cross-cultural understanding through its distinctive features.